ANALYSIS OF STUDENTS' MATHEMATICAL ABILITY IN SOLVING FRACTION PROBLEMS AT ELEMENTARY SCHOOL LEVEL - Sitti Fithriani Saleh; Sirajuddin; Ernawati; Nurhikma Damayanti (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract This research is qualitative research with a case study approach. This study aims to describe the level of students' problem-solving in fraction operations. The subjects of this study were three students of SDN 70 Manjalling who had low, moderate, and high abilities in solving fractions. Data were collected through written tests and individual interviews to obtain valid information. The results showed that students with high problem-solving abilities were able to apply all of Polya's problem-solving steps. Students with moderate problem-solving abilities could not do all of Polya's problem-solving steps. They only applied steps of understanding the problem and making a solution plan. Students with low abilities found it challenging to use fractions and were unable to use each step to solve the Polya's problem. Those students could only apply steps of understanding the problem and making a solution plan, but they did not understand the problem and could not convert it into mathematical forms.